Spartinivicinus ruber gen. nov., sp. nov., a Novel Marine Gammaproteobacterium Producing Heptylprodigiosin and Cycloheptylprodigiosin as Major Red Pigments - Huang, Zhaobin; Dong, Le; Lai, Qiliang; Liu, Jieqing (Frontiers in Microbiology, 2020)
The red pigment prodiginines are identified as bacterial secondary metabolites and display a wide range of bioactive properties. Here, a novel rose-red pigmented bacterium, designated strain S2-4-1HT, was isolated from coastal sediment of cordgrass Spartina alterniflora. Interestingly, it simultaneously produced heptylprodigiosin (C22H29N3O) and cycloheptylprodigiosin (C22H27N3O) as major red pigments, of which their chemical structures were established by liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR). Bioactive assays revealed that both heptylprodigiosin and cycloheptylprodigiosin had antibacterial and antifungal activities, and notably, cycloheptylprodigiosin showed stronger bioactivity than heptylprodigiosin. The complete genome of strain S2-4-1HT was determined to be 6,687,090 bp in length with G+C content of 40.13 mol%, including a circular chromosome with a size of 6,361,125 bp and three plasmids with a size of 141,078, 102,423, and 82,464 bp, respectively. The biosynthetic gene cluster of two red pigments was predicted on a ~41 kb gene fragment organized on the chromosome and displayed highly conserved features compared to several gammaproteobacterial species encoding the homologous genes. Finally, based on phenotypic, genotypic and chemotaxonomic characteristics, strain S2-4-1HT represented a novel genus-level species named Spartinivicinus ruber gen. nov., sp. nov. (type strain S2-4-1HT = MCCC 1K03745T = KCTC 72148T). Our study provided a novel bacterial source and novel prodigiosin analogs as promising pharmaceuticals in biotechnological application.